Single-Cell Analysis of the Multicellular Ecosystem in Viral Carcinogenesis by HTLV-1 - Koya, Junji; Saito, Yuki; Kameda, Takuro; Kogure, Yasunori; Yuasa, Mitsuhiro; Nagasaki, Joji; McClure, Marni B.; Shingaki, Sumito; Tabata, Mariko; Tahira, Yuki; Akizuki, Keiichi; Kamiunten, Ayako; et al. (Blood cancer discovery, 2021)
Premalignant clonal expansion of human T-cell leukemia virus type-1 (HTLV-1)-infected cells occurs before viral carcinogenesis. Here we characterize premalignant cells and the multicellular ecosystem in HTLV-1 infection with and without adult T-cell leukemia/lymphoma (ATL) by genome sequencing and single-cell simultaneous transcriptome and T/B-cell receptor sequencing with surface protein analysis. We distinguish malignant phenotypes caused by HTLV-1 infection and leukemogenesis and dissect clonal evolution of malignant cells with different clinical behavior. Within HTLV-1-infected cells, a regulatory T-cell phenotype associates with premalignant clonal expansion. We also delineate differences between virus- and tumor-related changes in the nonmalignant hematopoietic pool, including tumor-specific myeloid propagation. In a newly generated conditional knockout mouse model recapitulating T-cell-restricted (encoding PD-L1) gene lesions found in ATL, we demonstrate that PD-L1 overexpressed by T cells is transferred to surrounding cells, leading to their PD-L1 upregulation. Our findings provide insights into clonal evolution and immune landscape of multistep virus carcinogenesis. Our multimodal single-cell analyses comprehensively dissect the cellular and molecular alterations of the peripheral blood in HTLV-1 infection, with and without progression to leukemia. This study not only sheds light on premalignant clonal expansion in viral carcinogenesis, but also helps to devise novel diagnostic and therapeutic strategies for HTLV-1-related disorders.